Expanding the Potential of G‐Quadruplex Structures: Formation of a Heterochiral TBA Analogue. Issue 5 (12th February 2014) - Virgilio, Antonella; Varra, Michela; Scuotto, Maria; Capuozzo, Antonella; Irace, Carlo; Mayol, Luciano; Esposito, Veronica; Galeone, Aldo
Abstract In order to expand the potential applications of G‐quadruplex structures, we explored the ability of heterochiral oligodeoxynucleotides based on the thrombin‐binding aptamer (TBA) sequence to fold into similar complexes, with particular focus on their resistance in biological environments. A combination of CD and NMR techniques was used. Similarly to TBA, the ODN ggTTggtgtggTTgg (lower case letters indicate L residues) is able to fold into a chair‐like antiparallel G‐quadruplex structure, but has a slightly higher thermal stability. The discovery that heterochiral ODNs are able to form stable G‐quadruplex structures opens up new possibilities for their development in several fields, as aptamers, sensors and, as recently shown, as catalysts for enantioselective reactions.